2008
DOI: 10.1051/0004-6361:200809550
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of SZ and X-ray cluster detections

Abstract: Aims. We calibrate the number density, completeness, reliability, and the lower mass limit of galaxy-cluster detections through their thermal SZ signal and compare them to X-ray cluster detections. Methods. We simulate maps of the thermal SZ effect and the X-ray emission from light cones constructed in a large, hydrodynamical, cosmological simulation volume, including realistic noise contributions. The maps are convolved with linear, optimised, single-and multi-band filters to identify local peaks and their si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
0
19
1
Order By: Relevance
“…Pace et al (2008) found that ACT could detect tSZ halos down to 6 × 10 13 h −1 M fairly independent of redshift, whereas we have found that these halos become hard to detect at higher redshifts. The analysis of Pace et al (2008) only included the CMB as a foreground, so it is conceivable that the inclusion of point source foregrounds would degrade their forecasts for low-mass halos at high redshift, as we have found to be the case in our analysis. We also note that the analysis of Malte Schäfer & Bartelmann (2007) found that PLANCK could detect halos of mass 6 × 10 13 M h −1 below z = 0.1 when they included the CMB and all galactic foregrounds.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Pace et al (2008) found that ACT could detect tSZ halos down to 6 × 10 13 h −1 M fairly independent of redshift, whereas we have found that these halos become hard to detect at higher redshifts. The analysis of Pace et al (2008) only included the CMB as a foreground, so it is conceivable that the inclusion of point source foregrounds would degrade their forecasts for low-mass halos at high redshift, as we have found to be the case in our analysis. We also note that the analysis of Malte Schäfer & Bartelmann (2007) found that PLANCK could detect halos of mass 6 × 10 13 M h −1 below z = 0.1 when they included the CMB and all galactic foregrounds.…”
Section: Discussioncontrasting
confidence: 54%
“…Prospects for detection of tSZ clusters have been studied previously in the case of PLANCK (Malte Schäfer & Bartelmann 2007;Melin et al 2006), ACT (Pace et al 2008;Sehgal et al 2007), and SPT (Melin et al 2006), but these studies have mainly focused on the statistics of tSZ detections above the mass completeness limit of the respective surveys. Pace et al (2008) found that ACT could detect tSZ halos down to 6 × 10 13 h −1 M fairly independent of redshift, whereas we have found that these halos become hard to detect at higher redshifts.…”
Section: Discussionmentioning
confidence: 99%
“…Our method belongs to the matched filters developed for cosmic microwave background (CMB) observations (e.g. Schäfer et al 2006; Pace et al 2008) which use at once all available bands to obtain a unique response. With this respect, the algorithm presented here is a special case where a single band is considered, but could be naturally extended to include the full available colour information.…”
Section: Optimal Filter For Galaxy Overdensitiesmentioning
confidence: 99%
“…Optimal Filtering is a general technique to extract and measure an expected signal in a data-set affected by a noisy background. In astronomy, it was originally applied to weak lensing detection of galaxy clusters by Maturi et al (2005) and Pace et al (2007), and to X-ray and SZ detections in Pace et al (2008). In Bellagamba et al (2011), it was shown that in case of photometric detections, if one assumes that the background is homogeneous, the Optimal Filter actually corresponds to a Matched Filter.…”
Section: Introductionmentioning
confidence: 99%